Molecular structure, NBO analysis, ï¬rst hyper polarizability, and homo-lumo studies of Ï€-extended tetrathiafulvalene (EXTTF) derivatives connected to Ï€-nitro phenyl by density functional method - Abbaz, Tahar; Bendjeddou, Amel; Villemin, Didier (International Journal of Advanced Chemistry, 2018)
In these study we have been obtained the structural properties of (exTTF) derivatives 1-4 by using B3LYP/6-31G(d,p) of Density Functional Theory (DFT) utilizing Becke three exchange functional and Lee Yang Paar correlation functional. The calculation of ï¬rst hyperpolarizability shows that the molecules are attractive molecules for future applications in non-linear optics. Molecular electrostatic potential (MEP) at a point in the space around a molecule gives an indication of the net electrostatic effect produced at that point by the total charge distribution of the molecule. The calculated HOMO and LUMO energies show that charge transfer occurs within these molecules.Â